Physical and mechanical properties of Bi0.5(Na0.81K0.19)0.5TiO3 ceramic modified by KNbO3 - Suchittra Inthong (2019)
© 2019 Trans Tech Publications Ltd, Switzerland. This research reports the physical and mechanical properties of (1-x) Bi0.5(Na0.81K0.19)0.5TiO3-xKNbO3 (x=0.00-0.06) ceramics. The Modified Bi0.5(Na0.81K0.19)0.5TiO3 ceramics were synthesized by solid state reaction technique. The mixed oxides powders were calcined at 850 °C, 4 h and sintered at 1120 °C, 2 h to form pure phase perovskite and the optimum bulk density, respectively. The phase formation of the modified ceramic samples was determined by X-ray diffraction technique. All of the modified Bi0.5(Na0.81K0.19)0.5TiO3 ceramics exhibited a single perovskite phase. The bulk densities of the modified ceramic samples were 5.41±0.27-5.75± 0.28 g/cm3 using the Archimedes’ method. The microstructure was revealed by the scanning electron microscope. The rectangular-like shape was found of all studied ceramics which had the grain size between 1.31±0.02-1.56±0.03 µm. The mechanical properties were studied by both Vickers and Knoop microhardness tester. The results are discussed in term of the relation among hardness properties, Young’s modulus, and fracture toughness.